The i-process yields of rapidly accreting white dwarfs from multicycle He-shell flash stellar evolution models with mixing parametrizations from 3D hydrodynamics simulations. Issue 3 (12th July 2019) - Denissenkov, Pavel A; Herwig, Falk; Woodward, Paul; Andrassy, Robert; Pignatari, Marco; Jones, Samuel
ABSTRACT: We have modelled the multicycle evolution of rapidly accreting CO white dwarfs (RAWDs) with stable H burning intermittent with strong He-shell flashes on their surfaces for 0.7 ≤ M RAWD /M⊙ ≤ 0.75 and [Fe/H] ranging from 0 to −2.6. We have also computed the i-process nucleosynthesis yields for these models. The i process occurs when convection driven by the He-shell flash ingests protons from the accreted H-rich surface layer, which results in maximum neutron densities N n, max ≈ 10 13 –10 15 cm −3 . The H-ingestion rate and the convective boundary mixing (CBM) parameter f top adopted in the one-dimensional nucleosynthesis and stellar evolution models are constrained through three-dimensional (3D) hydrodynamic simulations. The mass ingestion rate and, for the first time, the scaling laws for the CBM parameter f top have been determined from 3D hydrodynamic simulations. We confirm our previous result that the high-metallicity RAWDs have a low mass retention efficiency (η 10 per cent ). A new result is that RAWDs with [Fe/H] -2 have η 20 per cent ; therefore, their masses may reach the Chandrasekhar limit and they may eventually explode as SNeIa. This result and the good fits of the i-process yields from the metal-poor RAWDs to the observed chemical composition of the CEMP-r/s stars suggest that some of the present-day CEMP-r/s stars could be former distant members of triple systems, orbiting close binary systems with RAWDs that may have later exploded as SNeIa.